Mathematical models and X-ray image analysis in the drying of cumbaru seeds - Cardoso Vilarinho, Marcella Karoline; Araújo da Silva, Tonny José; Magalhães Antoniacomi, Luis Augusto; dos Santos Oliveira, Andrea; Baptista da Luz, Petterson; Soares Alves Caldeira, Daniela; Pedroza Isquierdo, Eder; Carvalho Senigalia, Ritielly Laiany (Comunicata Scientiae, 2023)
The cumbaru (Dipteryx alata Vog.) is a native species of the Cerrado. The species is of great economic expression for family farming. This study aimed to determine the drying curves and fit mathematical models to the experimental data obtained in the drying of cumbaru seeds. Furthermore, it aimed to define the best-fitted model and correlate the damage caused by the drying process through X-ray images. The Dipteryx alata Vog. seeds were obtained from fruits collected from 20 matrices in the municipality of Cáceres, in the state of Mato Grosso (MT), approximately 255 days after anthesis. The seeds were extracted and stored for 15 days until they reached hygroscopic equilibrium and a 14.5% water content. Drying was conducted in a continuous airflow dryer with an approximate temperature of 40° and a constant airflow velocity of 2.5 m/s. The experimental data were fitted to twelve mathematical models. The values of the coefficients of determination (R2), the relative mean error (P), and the estimated mean error (SE) were used to check the models’ fit degree. After drying, 40 seeds from each treatment were subjected to X-ray testing using the Faxitron MX-20 DC 12 equipment. The Midilli mathematical model was the best fit for the experimental data. The X-ray images showed no cracks or any other damage caused by the drying process.